2020
DOI: 10.3390/cancers12102995
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 Is a Poor Prognosticator and Can Be Targeted by PVT1 Antisense Oligos in Gastric Adenocarcinoma

Abstract: Gastric adenocarcinoma (GAC) is inherently resistant or becomes resistant to therapy, leading to a poor prognosis. Mounting evidence suggests that lncRNAs can be used as predictive markers and therapeutic targets in the right context. In this study, we determined the role of lncRNA-PVT1 in GAC along with the value of inhibition of PVT1 using antisense oligos (ASOs). RNA scope in situ hybridization was used to analyze PVT1 expression in tumor tissue microarrays (TMAs) of GAC and paired normal tissues from 792 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Silencing of PVT1 by ASOs significantly inhibits the growth and invasion of GC cells. 184 Moreover, the CRISPR-Cas9 genome editing technique has been recognized as a potential therapeutic tool for cancer treatment by reactivating or silencing lncRNAs. For instance, GC metastasis associated long non-coding RNA (GMAN) can be disrupted by CRISPR-Cas9 through deleting the MFR region of GMAN, leading to downregulation of GC cell invasive activity.…”
Section: Clinical Implications Of Lncrnas In Gcmentioning
confidence: 99%
“…Silencing of PVT1 by ASOs significantly inhibits the growth and invasion of GC cells. 184 Moreover, the CRISPR-Cas9 genome editing technique has been recognized as a potential therapeutic tool for cancer treatment by reactivating or silencing lncRNAs. For instance, GC metastasis associated long non-coding RNA (GMAN) can be disrupted by CRISPR-Cas9 through deleting the MFR region of GMAN, leading to downregulation of GC cell invasive activity.…”
Section: Clinical Implications Of Lncrnas In Gcmentioning
confidence: 99%
“…Extensive studies have demonstrated that lncRNA PVT1 was a carcinogenic RNA (14). Li et al concluded that the expression of lncRNA PVT1 highly correlated with the poor prognoses of patients with gastric adenocarcinoma (15). Lu et al concluded that PVT1 regulated ferroptosis mediated by miR-214 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. concluded that the expression of lncRNA PVT1 highly correlated with the poor prognoses of patients with gastric adenocarcinoma ( 15 ). Lu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Among the eight prognostic ferroptosis-related lncRNAs (AL365181.3, MIR3142HG, PVT1, LINC01315, AL353804.1, HAGLR, AC005586.1, and AC245041.1) found in GC, PVT1 was signi cantly upregulated in gastric adenocarcinoma (GAC) compared to matched adjacent normal tissues. Its expression level was positively correlated with larger tumor size, deeper wall invasion, lymph node metastases, and short survival duration, indicating that PVT1 is a poor prognosticator as well as a therapeutic target in GAC (25). It is also a poor prognosticator of esophageal adenocarcinoma (EAC) as its expression was upregulated in EAC compared to paired Barrett's esophagus and normal esophageal tissues.…”
Section: Discussionmentioning
confidence: 99%